Vaginal chlamydial clearance following primary or secondary infection in mice occurs independently of TNF-α - Kamalakaran, Sangamithra; Chaganty, Bharat; Gupta, Rishein; Guentzel, M. N.; Chambers, James P.; Murthy, Ashlesh; Arulanandam, Bernard (Frontiers in Cellular and Infection Microbiology, 2013)
The role of TNF-α in chlamydial clearance is uncertain. Antibody-mediated depletion of TNF-α in mice and guinea pigs has been shown not to significantly affect chlamydial clearance, whereas production of TNF-α in addition to IFN-γ from T cells has been shown to correlate with enhanced clearance. The aim of our study is to evaluate the mechanistic role of TNF-α in clearance of primary and secondary chlamydial infection from the genital tract (GT) using C57BL/6 TNF-α deficient (TNF-α−/−) and wild type (WT) mice. Chlamydial shedding from the lower GT was evaluated following primary and secondary intravaginal challenge. Also, antibody and antigen specific cytokine responses were analyzed from the infected GT and spleens, and oviduct pathology determined to analyze the role of TNF-α in upper GT pathological sequelae. MHC II−/− mice, known to display muted adaptive immune responses and failure to resolve genital chlamydial infections, were used as a negative control. Following both primary and secondary genital chlamydial infection, TNF-α−/− mice exhibited elevated granzyme B production, but similar IFN-γ and antibody responses. Importantly, absence of TNF-α did not significantly alter the resolution of infection. However, TNF-α−/− mice displayed significantly reduced upper genital tract (UGT) pathology compared to WT mice. This study demonstrates mechanistically that optimal chlamydial clearance following primary and secondary chlamydial genital infection can occur in the complete absence of TNF-α, and considered with the reduction of upper GT pathology in TNF-α−/− mice, suggests that targeted induction of anti-chlamydial TNF-α responses by vaccination may be unnecessary, and moreover could be potentially pathogenic.